POLÍXENA, BY MARÍA GARCÍA ESPERÓN - Aquati, Claudio [UNESP]; Oliveira, Nicolas Pelicioni de [UNESP]; Silva, Gelbart Souza [UNESP]; Stradioto, Ilustracao de Edna Carla [UNESP] (Univ Estadual Paulista, Fundacao Editora Unesp, 2022)
In this chapter of El escudo de Aquiles, by Maria Garcia Esperon, Noche XIX: Polixena, in Olho d'agua magazine, it can be heard in portuguese language the voice of an in love Polyxena, in this never published livid and creative translation that is an example of modern narrative knotted from an exciting classical heritage. in Polyxena in addition to a retold myth of Troy, this notable mexican writer, in her hispanic words, explores the character's subjective personality in their many different Trojan War points of view with a particularly sensitive poetry, when referring to that trojan princess, which results of a character of beating heart, as she herself sings her sorrows of a cruel destiny, her talkative restlessness that silently stood inside of her, but here that restlessness left its taciturn behavior to change itself in a painful reflection about women's dignity and destiny.
Keywords: Achilles; classical reception; Polyxena; Trojan war